Direct shoot regeneration of Hibiscus rosa-sinensis L. cv. 'Brilliant Red' - Chew, Tiong Dar (2012)
Hibiscus rosa-sinensis cv. ‘Brilliant Red’, a five-petal, single-layered, and bright red perennial herb, is the national flower of Malaysia. For more than 50 years the local people recognise the status and sovereignty of this plant from the perspective of nationality, and even self-esteem. After decades of advancement in plant tissue culture field, propagation of Hibiscus spp. via in vitro method is starting to pick up its pace. So far, no report has been published to generate H. rosa-sinensis with fragrant flowers or flowers with longer life span. Under this context, plant tissue culture is a good means to produce large quantity of H. rosa-sinensis rapidly to cater for the market needs and pave ways for genetic manipulation of the plant for desired traits. A medium optimised for ‘Brilliant Red’ is yet to be formulated. Thus, this study reports on the effects of modifying the Murashige & Skoog (MS) medium in facilitating direct shoot regeneration from nodal explants of H. rosa-sinensis L. cv. ‘Brilliant Red’. The sterilisation conditions for 6 types of explants (basal leaf, leaf blade, leaf midrib, node, internode, and shoot tip) harvested from an open field were initially compared. The optimised sterilisation conditions for the explants were found to be 30% Clorox-15min exposure, 15% Clorox-30min exposure, 35% Clorox-15min exposure, 40% Clorox- 20min exposure, 10% Clorox-15min exposure, and 5% Clorox-40min exposure for the basal leaf, leaf blade, leaf midrib, node, internode and shoot tip, respectively. Using the optimised sterilisation conditions as mentioned, the survival-contamination percentages for each explant type were as follows: basal leaf: 86%, 0%; leaf blade: 99%, 0%; leaf midrib: 91%, 2%; node: 94.5%, 2%; internode: 97%, 0%; and shoot tip: 60%, 0%. In the direct shoot regeneration study using the nodal explants, MS medium containing 40 g/L sucrose, 0.3% (w/v) activated charcoal, and upplementations with myo-inositol,thiamine and nicotinic acid (Concentration: MS vitamin standard) were found to be suitable. The in vitro shoot survival rate was 30% with a mean leaf numbers of 2.7±0.45 produced, and a mean leaf length of 1.71±0.46 cm achieved after 5 weeks of culture on the modified medium. Callus induction from nodal explant could be performed by using 20 μM IBA, with callusing rate at 91.3±1.8% after 5 weeks of culture. Further histological study on the calli revealed that no embryogenic cell was found. Overall,shoot could be induced directly from H. rosa-sinensis cv. ‘Brilliant Red’ nodal explant based on the above formulation. More effort should be put on the indirect shoot regeneration. However, shoots maintenance required further refinement of the formulated MS medium. This study also reveals that callus induction could be an alternative way to produce H. rosa sinensis L. cv. ‘Brilliant Red’ in vitro plants.